INFO SYSTEM FOR ANALYSIS OF TECHNICAL AND ECONOMIC DEVELOPMENT OF THE USE OF WOOD FUEL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
EU Integration raises new requirements to energy sector, including municipal energy sector and improvement of local planning. Important role is assigned to development of energy infrastructure, use of renewable energy sources and energy efficiency. In order to use financial support from EU Structural funds for regional energy development, qualified applications will have to be developed in adequacy with the requirements for the use and control of EU Structural funds. The latter should be developed in the context of regional development programs (including energy sector development), which should be based on info systems. The Laboratory of Regional Energy Development at LEI is developing integrated info system "TAUSA" for this purpose. This info system is formed as server of data bases with respective bases and additional analysis modules. Information for the consumers of info systems could be available at Internet website. Besides indicators on district heating, "TAUSA" will accumulate data on distribution and end use of renewable energy sources at regional level, which permits to assess main macroeconomic indicators in the development of this economic activity. Matrix model for economic activity of preparing local fuel will enable to evaluate inter-branch links for district heating sector and the role of local fuel production in Gross Domestic Product (GDP) creating process. The macroeconomic model under development will help to assess economic benefit from the use of renewable energy sources in the region, including the facts that it improves employment, increases the flow of taxes to municipal budget, paid by the companies employed in this sector, give new business development opportunities.